Chromatic modernity : color, cinema, and media of the 1920s - Street, Sarah; Yumibe, Joshua (Columbia University Press, 2019)
"In Chromatic Modernity, Sarah Street and Joshua Yumibe provide a fascinating history of the use of color in film and consumer goods during the 1920s. They contextualize color's role in film, other art forms, and consumer culture to produce a comprehensive, comparative study that situates color cinema firmly within the culture of its time. With advances in technology, the use of color surged internationally and was applied to consumer goods, buildings, magazines, neon advertisements, and theatrical performances creating an exciting, chromatically rich visual culture. The use of color was not without its controversies, and the authors examine the intense debates during this period about color and its artistic, scientific, philosophical, and educational significance. Drawing on archives in the history of film, popular culture, and advertising, the authors consider such topics as the rise of the 'color consultant, ' the gendered nature of color, ideas of color psychology and consciousness in advertising and fashion, the standardization and experimentation of color in popular and avant-garde film, and how the rise of sound in cinema changed the use of color in film. Ultimately, the authors argue that this expansion of color across the international media environment demonstrates the extent to which it was forging new ways of looking at and experiencing the modern world"-- Provided by publisher.
Keywords: Color motion pictures -- History.; Color in advertising -- History.; Cinéma en couleurs -- Histoire.; Couleur dans la publicité -- Histoire.; PERFORMING ARTS -- Reference.; ART -- History -- Modern (late 19th Century to 1945); Color in advertising; Color motion pictures; History